Leakage of stomal effluent outside the baseplate leads to rise in product usage and health professional interactions. (12th January 2023) - de Fries Jensen, Lasse; Rolls, Natasha; Russell-Roberts, Paul; Vestergaard, Martin; Jensen, Majken Linnemann; Boisen, Esben Bo
Abstract : Background: Leakage of stomal effluent outside the baseplate that soils clothes or bedsheets is a common problem for many people with a stoma and significantly impacts their quality of life. Aim: To understand behavioural changes for people experiencing faecal leakage outside the baseplate regarding the usage of pouching systems, supporting products and interactions with health professionals. Methods: Retrospective, self-reported questionnaire. Findings: Respondents on average experienced 1.1 incidents of faecal leakage outside the baseplate per fortnight. In periods with issues of leakage, 21% of respondents had been in contact with health professionals, 40% increased their use of pouching systems, 25% increased their use of existing supporting products, and 21% included additional supporting products to their change routine. The increased use of healthcare resources was estimated to cost £32.47 in the 3 weeks following a leakage incident. Conclusion: Incidents of leakage outside the baseplate lead to increased use of healthcare resources.